Psychological determinants associated with vaccination intentions acceptance during pandemic events - A. Zartaloudi (European Psychiatry, 2022)
Introduction Psychological factors, like general self-efficacy, optimism or subjective well-being, might further enhance the understanding of why certain people vaccinate while others do not.